Exploration of the neuromodulatory properties of fyn and GSK-3β kinases exploiting 7-azaindole-based inhibitors - Marotta, Giambattista; Massenzio, Francesca; Ortega, Jose; Russo, Debora; Penna, Ilaria; Falchi, Federico; Babini, Giorgia; Petralla, Sabrina; Scarpelli, Rita; Roggiolani, Elena; Fricker, Gert; Rosini, Michela; et al. (Journal of medicinal chemistry, 2025)
The lack of efficient treatments and reliable biomarkers for neurodegenerative diseases requires the development of a late-stage powerful therapy. To this aim, we focused on Fyn and GSK-3β because both kinases are strictly involved in regulating neurodevelopmental processes, besides orchestrating neurotoxic aggregates’ deposition and neuroinflammatory processes development. Based on these premises, we developed dual kinase inhibitors to verify at the cellular level the suitability of Fyn and GSK-3β modulation in pursuing the recovery of neural trophism paired to the activation of a neuroprotective profile. Starting from the mild inhibitory potency of the 3-aminothiazole-7-azaindole scaffold, we identified nanomolar dual and selective inhibitors among the kinases of interest. In-depth biological evaluations were performed with the best compounds of the series to assess the neuroprotective and neuromodulatory properties, like enabling neurogenesis or glial polarization, as well as triggering immunomodulation with different patterns relating to their inhibitory profile, setting the stage for potential development of neuroregenerative treatments.
Online veröffentlicht: 8. August 2025
Gesehen am 15.01.2026